2021
DOI: 10.3390/su13105546
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Performance of Corrugated Cardboard as a Sustainable Sound-Absorbing and Insulating Material

Abstract: The continuing development of industrialization and increasing population density has led to the emergence of noise as an increasingly common problem, requiring various types of sound absorption and insulation methods to address it. Meanwhile, the recycling of resources to ensure a sustainable future for the planet and mankind is also required. Therefore, this study investigates the potential of corrugated cardboard as a resource for noise reduction. The sound absorption and insulation performance of non-perfo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 29 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…Panel AC-T3-BP exhibits better performance at low and medium frequencies and is, therefore, more suitable for applications in residential environments to reduce the reverberation time. The sound absorption performance of cardboard was evaluated by means of the impedance tube in [12]: non-perforated, perforated, and perforated with multi-frequency resonators configurations were tested. The results are compared with those presented in this study in Figure 13.…”
Section: Acoustic Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Panel AC-T3-BP exhibits better performance at low and medium frequencies and is, therefore, more suitable for applications in residential environments to reduce the reverberation time. The sound absorption performance of cardboard was evaluated by means of the impedance tube in [12]: non-perforated, perforated, and perforated with multi-frequency resonators configurations were tested. The results are compared with those presented in this study in Figure 13.…”
Section: Acoustic Testsmentioning
confidence: 99%
“…One of the most striking cases of designing packaging also considering its reuse is the one proposed by Heineken [7], which realized square glass bottles that were used to build houses in the Caribbean islands. Also the scientific community has realized the potential of end-of-life materials [8], and several studies have investigated the properties of plastic bottles [9,10], cardboard and paper elements [11][12][13][14][15][16], Tetra-Pak panels [17], textiles waste [18][19][20][21][22], and egg boxes and trays [23][24][25][26][27][28]. More recently, so-called green and sustainable materials made of natural fibers have been investigated [29][30][31][32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kang et al [25] conducted experiments with both sinusoidal and trapezoidal perforated corrugated cardboard (PCC). The result revealed that the noise reduction coefficient (NRC) of sinusoidal and trapezoidal PCC is 0.346 and 0.307.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, sound absorption and sound insulation are essential features in humanoccupied buildings. Synthetic fibers are used traditionally as sound-absorbing materials, but in recent years, "green" sound-absorbing materials have gained research attention due to a growing interest in environmental issues [4][5][6][7]. Natural fibers are biodegradable, eco-friendly materials produced from plants, animals, and minerals.…”
Section: Introductionmentioning
confidence: 99%